Pharmacokinetics and tissue distribution of four major bioactive components in rats after oral administration of Xianglian pill. (19th January 2020) - Lu, Min; Chu, Zixuan; Wang, Liying; Liang, Chen; Sun, Peilu; Xiong, Shan; Mu, Yanling
Abstract: Xianglian pill, a TCM prescription, consists of Rhizome Coptidis and Radix Aucklandiae, and has been used to treat gastrointestinal disease for many years. Berberine, jatrorrhizin, coptisine and palmatine are four representative alkaloids in Xianglian pill. Knowing that the drug disposal process in vivo is closely related to the toxicity and efficacy of a drug, it is important to classify the disposal properties of these alkaloids. In this study, the pharmacokinetics and tissue distribution of the four alkaloids were investigated. The analytical samples were analyzed using a validated HPLC–MS/MS method. The results showed that the four alkaloids could be slowly absorbed. The C max values of berberine, jatrorrhizin, coptisine and palmatine were 11.420, 2.287, 2.584 and 3.102 ng/ml, respectively. Subsequently, the tissue distribution studies showed that they were quickly distributed to various tissues with rich blood flow in the body.